2016
DOI: 10.1007/s10584-016-1638-9
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to renal, heat and respiratory hospitalizations during extreme heat among U.S. elderly

Abstract: Background Extreme heat (EH) is a growing concern with climate change, and protecting human health requires knowledge of vulnerability factors. We evaluated whether associations between EH (maximum temperature > 97th percentile) and hospitalization for renal, heat and respiratory diseases among people ≥ 65 years differed by individual and area-level characteristics. Methods We used Medicare billing records, airport weather data, U.S. Census data and satellite land cover imagery in 109 US cities, May-Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 44 publications
3
52
0
2
Order By: Relevance
“…Most studies suggest that the very old and the very young are most vulnerable (Basu 2002; Gronlund et al 2016; Isaksen et al 2015; Kravchenko et al 2013; Semenza et al 1999). During the heat waves in 1980 in St. Louis, Missouri and in 1995 in Chicago, mortality rates among people with chronic diseases, the very old or young, those of low socioeconomic status, and urban dwellers tended to be higher when compared to the general population (Jones et al 1982; Semenza et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies suggest that the very old and the very young are most vulnerable (Basu 2002; Gronlund et al 2016; Isaksen et al 2015; Kravchenko et al 2013; Semenza et al 1999). During the heat waves in 1980 in St. Louis, Missouri and in 1995 in Chicago, mortality rates among people with chronic diseases, the very old or young, those of low socioeconomic status, and urban dwellers tended to be higher when compared to the general population (Jones et al 1982; Semenza et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerability may vary according to sex; during the California heat wave of 2006, the mortality rate among women was higher than among men (Knowlton et al 2009). In addition, several studies in multiple U.S. locations found an increased risk for heat-associated mortality among African Americans as compared to whites (Gronlund et al 2016; Kravchenko et al 2013; McGeehin and Mirabelli 2001; Semenza et al 1999). However, other studies failed to find differences in vulnerability by race (Green et al 2010; Groulund 2014; Madrigano et al 2013; Pillai et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Die Häufigkeit variierte in Abhängigkeit von dem jeweilig untersuchten Wohnort (Grünflächen in der Nachbarschaft, Anteil Wohnfläche mit Air-Conditioning, Alter der Immobilie usw.) [32].…”
Section: Diskussionunclassified
“…A major issue with the V-shaped relationship developed in Martens (1998) andutilised in Tol (2002a) is that it has been found to be biased towards cold-related mortality and that this is likely to have led to bias towards finding a net reduction in mortality associated with climate change (Huber et al 2017). As previous studies have found different shapes for the temperature-mortality relationship depending upon the city/climate focused upon (Analitis et al 2008;Gasparrini et al 2015;Gasparrini et al 2017;Gosling et al 2009;Gronlund et al 2016;Guo et al 2014); it is likely that the application of a coldbiased temperature-mortality relationship to tropic, sub-tropic and temperate regions with warm summers will be problematic. The importance of assessing the nature of the temperature-mortality relationship using different techniques and data from a range of climatic regions is important as previous studies, which includes Guo et al…”
Section: Introductionmentioning
confidence: 93%